2022
DOI: 10.1136/bmj-2021-064604
|View full text |Cite
|
Sign up to set email alerts
|

The effects of plasma exchange in patients with ANCA-associated vasculitis: an updated systematic review and meta-analysis

Abstract: Objective To assess the effects of plasma exchange on important outcomes in anti-neutrophil cytoplasm antibody (ANCA)-associated vasculitis (AAV). Design Systematic review and meta-analysis of randomised controlled trials. Eligibility criteria Randomised controlled trials investigating effects of plasma exchange in patients with AAV or pauci-immune rapidly progressive glomerulonephritis and at least 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 29 publications
(55 reference statements)
1
53
0
12
Order By: Relevance
“…We used the control group event rates in the systematic review to estimate the baseline risks for outcomes of mortality, serious infections, and relapse of AAV, and used the data from seven multinational RCTs conducted by the European Vasculitis Study Group with 798 patients to estimate the baseline risk for the outcome of ESKD 23242526272829. The systematic review found no credible evidence that the relative effect of plasma exchange would vary on the basis of kidney function or pulmonary haemorrhage 12. We therefore used the baseline risks, along with the pooled relative risk for overall patients at the timeline of one year and long term follow-up (median 3 years) from the systematic review, to calculate the absolute effect estimates presented in our evidence summaries.…”
Section: The Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…We used the control group event rates in the systematic review to estimate the baseline risks for outcomes of mortality, serious infections, and relapse of AAV, and used the data from seven multinational RCTs conducted by the European Vasculitis Study Group with 798 patients to estimate the baseline risk for the outcome of ESKD 23242526272829. The systematic review found no credible evidence that the relative effect of plasma exchange would vary on the basis of kidney function or pulmonary haemorrhage 12. We therefore used the baseline risks, along with the pooled relative risk for overall patients at the timeline of one year and long term follow-up (median 3 years) from the systematic review, to calculate the absolute effect estimates presented in our evidence summaries.…”
Section: The Evidencementioning
confidence: 99%
“…Because of availability of baseline risk strata, the linked systematic review provided the absolute effects of plasma exchange in ESKD and serious infections in a time frame of 1 year rather than a longer time frame 12. Plasma exchange probably reduces the 1 year risk of ESKD (the absolute risk reduction approximately 0.1% in low risk group, 2.1% reduction in low-moderate risk group, 4.6% reduction in moderate-high risk group, and 16.0% in high risk group or patients requiring dialysis) but increases the risk of serious infections (the absolute risk increase approximately 2.7% in low risk group, 4.9% in low-moderate risk group, 8.5% increase in moderate-high risk group, and 13.5% in high risk group or patients requiring dialysis) at 1 year (moderate to high certainty).…”
Section: The Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Related systematic reviews [ 15 , 16 ] have been published in 2016, which have conducted comprehensive literature search and identified eligible ME studies published before 2015. By adopting the common practice of previous updated systematic reviews [ 25 , 26 ], we referred to the search strategies of previous systematic review [ 15 ] and searched PubMed, Embase, and Web of science with "meta-epidemiology", "treatment effect" and related keywords from January 2015 to August 2020. Reference lists of previously published systematic reviews [ 15 , 16 ] as well as the identified ME studies were screened for additional studies.…”
Section: Methodsmentioning
confidence: 99%
“…Jedoch konnte gezeigt werden, dass unter niedriger dosierten Glukokortikoiden bei gleichen Remissionsraten Infektionen reduziert werden können. Daher werden in neueren Therapiestrategien Steroide schneller reduziert 43 .…”
Section: Therapieunclassified